Kepemimpinan Islami Dan Etika Kerja Islam: Bagaimana Keduanya Mempengaruhi Kinerja Karyawan Dengan Motivasi Kerja Sebagai Variabel Intervening - Rizqon Hoeroni; Ahmad Gunawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Employee performance is one of the important factors in determining the success of an organization. Employee performance can be affected by a variety of factors, including Islamic leadership and Islamic work ethics. Islamic leadership is a leadership style that is based on Islamic values, whereas Islamic work ethics is a set of values and norms that govern the work behavior of a Muslim. This study aims to examine the influence of Islamic leadership and Islamic work ethics on employee performance with work motivation as an intervening variable. This research uses quantitative methods with a survey approach. The study population were employees in a private company in Indonesia. The study sample amounted to 95 employees who were taken randomly. Data was collected through questionnaires. The results of the study are as follows: Islamic Leadership has a positive and significant influence on Work Motivation, Islamic Work Ethics has a positive and significant influence on Work Motivation, Islamic Leadership has a positive and significant influence on performance, Islamic Work Ethics has a positive and significant influence on performance, Work Motivation has a positive and significant effect on performance, Islamic Leadership has a positive and significant effect on Performance through Work Motivation, this means that work motivation can mediate between Islamic leadership variables and performance variables and shows that Islamic Leadership can be used as a variable that can improve performance, Islamic Work Ethics has a positive and significant effect on Performance through Work Motivation, this means that work motivation can mediate between Islamic work ethics variables and performance variables and shows that Islamic work ethics can be used as variables that can improve performance. Keywords: Islamic leadership, Islamic work ethic, work motivation, employee performance.